Utility of Routine Stool Examination in Young Patients with Microcytic Hypochromic Anaemias - Muhammad Tariq Baqai , Munazza Nazir , Ameera Khurshid (Journal of Rawalpindi Medical College, 2018)
Background: To study the utility of routine stool examination in patients with microcytic hypochromic anaemia in a semi-urban/rural setting Methods: This prospective observational study was conducted at Sheikh Khalifa Bin Zaid (SKBZH) CMH Hospital in Muzaffarabad, Azad Jammu and Kashmir. Two hundred patients , 110 females and 90 males, between the age of 5 to 18 years with clinical features of anaemia were included in the study. They presented from Muzaffarabad and its adjoining areas in the Paediatric and Medical OPD of the hospital. Complete blood picture was done in all patients and routine stool examination was also advised Results: Fifty- seven (28.4%) patients did not submit stool for examination . Thirty-two (15.9%) did not collect results from the laboratory. Stools for ova and parasite/ cyst was reported in 14.3% (20) patients while they gave no such information in 45%(91) Conclusion: Stool examination should be advised as an initial test for investigation of microcytic hypochromic anaemia as it has a significant yield in young patients in a rural setting. Where financial or other circumstances in the young do not permit this test or specific investigations for iron deficiency , a low haemoglobin coupled with low MCV,MCH and MCHC should be empirically treated with anti-helminths and iron supplements and the clinical response gauged.